A Conceptual Framework On The Factors Influencing Halal Consumption: An Exploratory Study Among Muslim Consumers In Malaysia - Abdul Khalek, Aiedah; Syed Ismail, Sharifah Hayaati (Online Journal of Research in Islamic Studies, 2015)
Earlier researchers discussed the three main factors which are attitude, subjective norms and perceived behavioral control in explaining halal consumption. However, by reviewing previous literatures, analyzing the international trends of halal consumption and the Islamic rulings of halal consumption, religiosity could be considered as an important variable influencing halal consumption. Religiosity factor has been empirically proven by previous studies in different countries. Therefore, this paper aims to contribute to the current literature by integrating religiosity factor in predicting halal consumption among Muslim consumers. An exploratory study is conducted to investigate the influence of attitude, subjective norms, perceived behavioral control and religiosity in influencing halal consumption. The findings of this study reveal that religiosity is the strongest factor among all in influencing halal consumption. It is anticipated that the arguments presented in this paper would spring up further discussion in this field and encourage more empirical research to be conducted.